Les aidantes francophones dans les communautés francophones et acadiennes du Canada - Bérubé, Allison; Lemire, Jacinthe; Gagné-Ouellette, Murielle; Ouellette, Myriane (Alliance des femmes de la francophonie canadienne, 2021)
Un des objectifs de l’AFFC est d’organiser un forum national sur les personnes aidantes qui se tiendra en 2022. Pour ce faire, elle désire mettre à jour les recommandations de son étude de 2010 intitulée Les aidantes francophones dans les communautés francophones et acadiennes du Canada. Cette étude, composée de cinq phases, s’étend de 2006 à 2010. Le présent Livre blanc se base donc sur les données recueillies dans l’étude de 2006, qui s’est poursuivie en 2010, pour dresser un portrait actuel des personnes aidantes de la francophonie canadienne et acadienne. Il vise à mettre en lumière leurs réalités et les ressources qu’ils ont à disposition, et ainsi émettre des recommandations qui répondront à leurs besoins. La création du présent Livre blanc a nécessité la réalisation de quatre différentes étapes afin d’être en mesure de recueillir les données essentielles à la mise à jour de l’étude de 2010 : 1. Une recension des écrits portant sur les conditions de vie des personnes aidantes francophones du Canada afin de présenter les grandes lignes de ces récentes études. 2. Une recension des services et ressources disponibles pour répondre aux besoins des personnes aidantes. Cette recension peut également être utilisée pour construire une banque de ressources destinée aux personnes aidantes francophones du Canada et ailleurs. 3. Un sondage et des entrevues téléphoniques semi-dirigées ont été réalisés auprès de personnes aidantes francophones et acadiennes du Canada pour dresser un portrait actuel de leur situation. 4. Un suivi des retombées des trois projets pilotes développés par l’AFFC au cours de la Phase 3 de l’étude de 2010.
Nombre de pages: 89

Naviguer le maintien à domicile en communautés de langue officielle en situation minoritaire rurales : enjeux et pistes de solutions - Dupuis-Blanchard, Suzanne; Caissie, Julie (Reflets, 2021)
Le vieillissement de la population dans les provinces de l’Atlantique est une réalité courante en plus d’une composition géographique rurale et la présence de communautés de langue officielle en situation minoritaire (CLOSM). Les objectifs de cette étude descriptive qualitative étaient de 1) comprendre les services utilisés pour le maintien à domicile, et 2) déterminer les services nécessitant une amélioration pour l’accès en français. Vingt-six (n=26) personnes âgées ont participé à cette étude en région rurale de l’île du Prince Édouard. Les résultats témoignent des difficultés d’accès aux services pour le maintien à domicile tout en offrant des pistes de solutions pour l’améliorer. Mots-clés : Maintien à domicile, vieillissement, communautés de langue officielle en situation minoritaire, communauté rurale, services, recherche qualitative

Being small and outnumbered: Service and sociocultural exclusion among older linguistic minorities in Finland - Nyqvist, Fredica; Björklund, Siv; Lindell, Marina; Nygård, Mikael (Linguistic Minorities and Society, 2021)
Our study aims to analyze the social exclusion of older Swedish and Finnish speakers living as linguistic minorities in bilingual municipalities in Finland, where municipal authorities are required to offer services in both languages. Data was taken from the 2016 Language Barometer Survey, measuring the quality of language services in bilingual municipalities (n=33). For the purposes of our study, we focused on 2,030 people between the ages of 60 and 84. We included four different language groups, unilingual Swedish and Finnish speakers and Finnish-Swedish bilinguals and examined two social exclusion domains: service and sociocultural exclusion. The results showed that living as a regional minority poses a greater challenge when it comes to social inclusion for the unilingual and bilingual Swedish minority, as opposed to the Finnish-speaking minority. We conclude that linguistic rights seem to be achieved in the most egalitarian way in bilingual municipalities where Swedish is the majority language. Keywords: older adults, linguistic minority, bilingual, social exclusion, Finland

Social exclusion among official language minority older adults: A rapid review of the literature in Canada, Finland and Wales - Nyqvist, Fredica; Häkkinen, Emilia; Renaud, Alexandre; Bouchard, Louise; Prys, Cynog (Journal of Cross-Cultural Gerontology, 2021)
It has been suggested that older adults from minority linguistic and ethnic communities face higher risks of being socially excluded. The aim of this review was, therefore, to explore and review social exclusion studies conducted among official language minority older adults in three countries, namely Canada, Finland and Wales. A rapid review approach was used to review scientific literature in line with six social exclusion domains. The literature searches were made in Finnish, Swedish, English, French and Welsh and were restricted to research published within the timeline of 2001 – September 2019 and yielded 42 articles. The included studies were categorized into three different domains: socioeconomic influences, social participation and societal conditions. Converging and diverging patterns of social exclusion in old age were identified between the linguistic minorities. Linguistic barriers regarding access to health care and receiving health information were common across the three linguistic contexts, whereas exclusion from social participation was noticed amongst the linguistic minorities in Canada and Wales. Some connections between belonging to a linguistic minority and being exposed to a lower socioeconomic status and higher poverty risk were made, however, these findings were not robust across all three countries. The findings indicated that experiences of exclusion could be considered fairly common among linguistic minority older adults. We conclude that the research evidence presented in the review sheds light on issues of social inequality in old age between linguistic majorities and minorities, thus identifying important aspects of social exclusion to guide future research as well as policy and practice.

Strategies to improve French language health and social service continuity for seniors in Ontario and Manitoba - Savard, Jacinthe; Savard, Sébastien; de Moissac, Danielle; Giasson, Florette; Kubina, Lucy-Ann (Linguistic Minorities and Society, 2021)
Access to health and social services in one’s official language of choice is an important component of quality and safety of care for seniors. Access can be fragmented, even in the context of legislation guaranteeing the right to receive such services, and in areas with a higher proportion of bilingual providers. Using a community-based participatory approach, we identified mechanisms promoting or impeding the clinical integration of health and social French language services intended for seniors living in two Canadian Francophone minority communities. Thirteen recommendations highlight the possibility for new initiatives to promote a continuum of French language health and social services in a minority context, involving collaboration among a variety of actors at all levels of our analytical framework: service trajectory (providers); francophone communities; organizational; political and regulatory; and symbolic (values) structures. Keywords: seniors, linguistic minorities, service integration, health and social services, continuity of care

Le vieillissement francophone en contexte minoritaire. Défis et opportunités - Siméon, Frantz; Couturier, Yves (Reflets, 2021)